Enhanced volatile fatty acids production from waste activated sludge anaerobic fermentation by adding tofu residue. (February 2019) - Huang, Xiaoding; Zhao, Jianwei; Xu, Qiuxiang; Li, Xiaoming; Wang, Dongbo; Yang, Qi; Liu, Yang; Tao, Ziletao
Graphical abstract: Highlights: Adding TR into WAS enhanced VFA production and shortened fermentation time. TR + WAS promoted sludge solubilization, hydrolysis and acidogenesis processes. TR + WAS posed a positive synergetic effect on lignocellulose hydrolysis. Appropriate amounts of mineral elements in TR benefited solubilization. Iron and calcium in TR contribute to the phosphorus removal in fermentation liquor. Abstract: In this study, an economical and eco-friendly strategy (i.e., adding tofu residue (TR) into waste activated sludge (WAS)) to enhance volatile fatty acid (VFA) production was reported. Experimental results indicated that the maximal VFA yield at T/W ratio (TR/WAS, the ratio of the volatile suspended solids (VSS)) of 0.64 on 5 d was 240.8 mg COD/g VSS, which was 10.2 and 1.1-fold of that in sole WAS and sole TR, respectively. The feasible fermentation time was shortened by 2 days, as compared with sole WAS or sole TR. Mechanism investigation showed that the addition of TR promoted solubilization, hydrolysis, and acidogenesis processes. The synergistic effect of microorganisms contained in TR and WAS may be responsible for the enhancement of lignocellulose hydrolysis and VFA generation. Appropriate amounts of mineral elements in TR benefited solubilization, the soluble iron and calcium in TR could contribute to the phosphorus removal in fermentation liquor.